2002
DOI: 10.1046/j.1365-3180.2002.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liquid manure application method on weed control in spring cereals

Abstract: Summary Injection of liquid manure (slurry) into the soil is an alternative to the traditional surface application. By the injection method, it is possible to place nutrients closer to the crop sown, thus offering the crop a competitive advantage over weeds. This study compares the response in crop yield, weed density and weed biomass to injection vs. surface application of liquid manure through three growing seasons in barley and oats. The manure applications were combined with treatments of weed harrowing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Increasing the N rate in the LMP soil class was most beneficial to the velvetleaf grown in mixture, as maize interference in velvetleaf decreased with increasing N rate (Figure 2). These results are congruent with previous studies that have demonstrated the reduced competitive ability of weed species at low soil N levels (Blackshaw et al 2003;Bonifas et al 2005;Dyck et al 1995;Menalled et al 2004;Rasmussen 2002). In maize, velvetleaf interference tended to decrease in response to increasing N rate in the LMP soil, but the effect was not significant (P 5 0.11; Figure 2).…”
supporting
confidence: 93%
“…Increasing the N rate in the LMP soil class was most beneficial to the velvetleaf grown in mixture, as maize interference in velvetleaf decreased with increasing N rate (Figure 2). These results are congruent with previous studies that have demonstrated the reduced competitive ability of weed species at low soil N levels (Blackshaw et al 2003;Bonifas et al 2005;Dyck et al 1995;Menalled et al 2004;Rasmussen 2002). In maize, velvetleaf interference tended to decrease in response to increasing N rate in the LMP soil, but the effect was not significant (P 5 0.11; Figure 2).…”
supporting
confidence: 93%
“…For implementation of more appropriate techniques, digestion of slurry and organic residues can constitute an important key technology by reducing solid concentration and particle sizes (Martin 2004;Masse et al 2004;Dahlin et al 2005). Direct injection of liquid manure has, additionally, a potential to improve the crop's competitiveness with weeds (Rasmussen 2002;Petersen 2005). A solid-liquid separation of the effluents after digestion should be a technique for further improvement of the NUE of the nutrients circulating within organic farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…Petersen (2001) and Petersen and Mortensen (2002) reported that nitrogen uptake and dry matter production increased, when the distance from crop row to fertilizer band decreased. Furthermore, the shorter the distance from the plant to fertilizer, the more vigorous is the plant growth (Cochran et al, 1990;Rasmussen, 2002). In the present study, the weeds grew more vigorously in IR than in BR by uptake of nutrients from the fermented organic fertilizer applied in IR.…”
Section: Comparison Of the Relationship Of Vcr With Weedmentioning
confidence: 44%